Study case on simulation an active filter based on load DC motor - Yusuf Lada, Musa; Bugis, Ismadi; Talib, Md Hairul Nizam (2010)
Nowadays power system facing serious problem with power quality in terms of power factor and harmonics due to increasingly number of nonlinear load. This paper will discuss about the effecting of dc motor by using an active filter on the power system. The simulation had been done by using MATLAB/ Simulink. The Voltage source shunt active filter (VSAF) has been used in this simulation with the common DC bus. The p-q theorem will be used to control the PWM switching of the active filter. Simulation result shows that by using a Series DC motor as load on active filter the line current will compensate and reduce the THD of the line current.